Involvement and Therapeutic Potential of the GABAergic System in the Fragile X Syndrome - Inge Heulens; Charlotte D'Hulst; Sien Braat; Liesbeth Rooms; R. Frank Kooy (The Scientific World Journal)
Many drugs have been developed that are able to modulate the GABAergic system, which is involved in anxiety, depression, epilepsy, insomnia, and learning and memory. The recent observation that the GABAA receptor is underexpressed in the fragile X syndrome, an inherited mental retardation disorder, therefore raised hopes for targeted therapy of the disorder. This review summarizes the lines of evidence that demonstrate a malfunction of the GABAergic system. The GABAergic system clearly emerges as an attractive target for therapy of the fragile X syndrome, and thus provides an excellent example of how genetic research can lead to unique opportunities for treatment.